Disease X vaccine production and supply chains: risk assessing healthcare systems operating with artificial intelligence and industry 4.0 - Radanliev, P; De Roure, D (Springer, 2023)
Objective: The objective of this theoretical paper is to identify conceptual solutions for securing, predicting, and improving vaccine production and supply chains.